Social justice in pandemic immunization policy: We're all in this together. (September 2021) - Torrie, Carmen; Yanicki, Sharon; Sedgwick, Monique; Howard, Lisa
Policy decisions regarding immunization during a pandemic are informed by the ethical understandings of policy makers. With the possibility that a vaccine might soon be available to mitigate the deadly COVID-19 pandemic, policy makers can consider learnings from past pandemic immunization campaigns. This critical analysis of three policy decisions made in Alberta, Canada, during the 2009 H1N1 influenza pandemic demonstrates the predominance of distributive justice principles and the problems that this created for vulnerable groups. Vulnerable groups identified in Alberta include rural and First Nations populations. We propose a social justice approach as a viable alternative to inform pandemic immunization policy and invite debate.